ANALYSIS OF FACTORS RELATED TO PREVENTION OF DIARRHEA IN TODDLERS - Ningsih, Triana; Yansyah, Eka Joni; Sarwoko, Sabtian; Marita, Yulis (LPPM STIKES Al-Ma'arif Baturaja, 2026)
Diarrhea is one of the leading causes of death among children worldwide, with approximately 443,832 deaths in 2023 and nearly 1.7 billion cases annually. This study aims to identify factors associated with the prevention of diarrhea in children at the Rasuan Community Health Center in East OKU Regency. The study design used a cross-sectional method with a sample of 50 respondents obtained through accidental sampling. Univariate results showed that 76% had high diarrhea prevention, 56% had poor knowledge, 72% had poor hygiene behavior, and 60% had poor access to services. Bivariate results showed a relationship between education (p = 0.032) and hygienic behavior (p = 0.002) with diarrhea prevention, while knowledge (p = 0.416) and access to services (p = 0.182) were not significantly related. Education and hygienic behavior factors influence diarrhea prevention in toddlers. Health education efforts need to be improved, using simple, communicative media and involving village cadres to reach the community directly.